Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Xin, Ni; Li, Zhao; Jiang, Yong-Wei; Wang, Hui; Tan, Juan; Li, Yang; Sun, Bing-Jiao; Lin, Xiao-Long (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. The null model results showed the main factor that affected the distribution of fish in the Liaohe National Park is the stochastic processes. Among the deterministic processes, the main environmental filter factors affecting fish community structure include dissolved oxygen and total hydrargyrum. Overall, our study highlighted that the fish community was influenced by a combination of both deterministic and stochastic processes. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.